Evaluation of pulse modulation settings for optimal pop-dusting efficiency using the Quanta Litho 150 laser: An in vitro study - Victor Sandoval; Stephen Hassig; Mitchell Hoestermann; Connor Bittlingmaier; Regan Merkin; George K. Siodis; Thomas Osinski; Nitin Sharma; Rajat Kumar Jain; Scott Quarrier (Urology Annals)
Purpose: The novel Quanta Litho 150 W (Samarate, Italy) was recently introduced and incorporates new pulsed modulation settings. We sought to analyze ablation rate and efficiency in short pulse (SP), virtual basket (VB), and vapor tunnel (VT) pulsed modulations, in an in vitro pop-dusting simulation across different settings at a fixed power of 30 Watts (W) and fixed periods of time. Materials and Methods: Seven millimeter BegoStone phantoms were subjected to lithotripsy in a simulated calyx using Holmium: yttrium:aluminum garnet Quanta System 150 W. 30 W was applied at different settings across three pulse modulation modes: SP, VB, and VT. Ablation rate and efficiency were and compared between the three groups. Results: Maximum ablation efficiency for the VB and VT groups was achieved at VB 2J x 15 Hz and VT at 2.5 J x 12 Hz. Ablation efficiency decreased with higher Joules. VB at 1.5 J x 20 Hz and SP at 2.5 J x 12 Hz were the only settings to obtain 85% ablation at 5 min. Conclusions: In vitro laser lithotripsy using a BegoStone phantom, VB at 2J x15 Hz and VT at 2.5 J x 12 Hz were the most efficient setting for pop-dusting with the Quanta Litho 150. The highest efficiency (mg/min) was achieved with VB at 2 J x 15 Hz and VT at 2.5 J x 12 Hz at 1:15 min.